The making of "asli" Sumba woven cloth: how globalising "intangible heritage" impacts women's roles. Issue 8 (16th November 2020) - Untari, Rustina; Gajjala, Radhika; Sanjaya, Ridwan
ABSTRACT: This article discusses how the production of "original"/" asli " commodity through a local/global dialectic in how "intangible heritage" is defined and how contemporary global market-facing Sumba weaving contributes to shifts and contradictions in gender roles as they are shaped simultaneously through local community needs and through a global facing westernised patriarchal business ethos. The increasing global north facing integration of global south production communities into the world markets for instance, leads to a masculinisation of management and global facing leadership while along with a feminisation of the local production process. Evidence for our observations were drawn from over 50 in-depth interviews and onsite observation during field visits to the site.